InAlN-based LEDs emitting in the near-UV region. (23rd May 2019) - Pampili, Pietro; Zubialevich, Vitaly Z.; Maaskant, Pleun; Akhter, Mahbub; Corbett, Brian; Parbrook, Peter J.
Abstract: Fully functional InAlN-based ultraviolet LEDs emitting at 340–350 nm were demonstrated for the first time; detailed electrical and optical characterization is presented and discussed. Results from the measurements at pulsed conditions are in agreement with the attribution of the dominant electroluminescence peak to near-band-edge emission. The composition of the AlGaN barriers was chosen to give the same internal polarization field as that of the InAlN wells. A simulation study of this polarization-matched heterostructure shows a significant increase in the electron-hole overlap integral if compared with a standard AlGaN/AlGaN active region having the same level of carrier confinement. Limitations and problems of these preliminary devices are also presented, and possible future work aimed at increasing their efficiency is discussed.